Simulation of ingestion of flammable gas mixture by a gas turbine compressor in CFX - Hu, Ting (2016)
Gas Turbine is efficient machine for converting fuel into energy at near design point. This project draws the boundary conditions from one known operating point on the operation of an industrial and marine gas turbine LM 2500 to simulate with CFX software. Normal operations see combustion taking place only within the combustor as that is the only point fuel is introduced. A large gas leak (high flow rates) scenario gives rise to the possibility that the flammable gas passes through the filters before the filter doors are shut. In such a plausible scenario, combustion could take place outside the combustor. This project seeks to understand and preliminarily simulate hot surfaces causing combustion within the first stage of the LM 2500 compressor and the conditions that support this. The investigation would be carried out computationally.